Ontology of laughter: social-ethical aspects - Stebelska, Olexandra (Східноєвропейський національний університет імені Лесі Українки, 2018)
Laughter is very important emotional manifestation for human being. The understanding of laughter’s nature and the determination of its main characters can’t be ignored because laughter is the ability that characterizes and determines the very human way of seeing and understanding the world and the person himself. As a result of the critical analysis, such laughter features as paradoxicality, distancing, openness, freedom, sociality, connection with the sphere of morality are noted and simultaneously indicate the internal unity of consciousness and laughter nature. Laughter built into the structure of human consciousness, and therefore it acquires an ontological character. The article focuses on the social nature of laughter and its educational function. Gradually and consistently, the chain of “consciousness-conscience-laughter-shame” was built during this research. As laughter sometimes can be put in pair with evil, very often the researchers consider it sinful. It was shown that the roots of evil lie not in laughter, but in the person who manipulates its inner abilities.
Keywords: consciousness; conscience; laughter; evil; paradox; distancing; freedom; power; sociality